PENAMBAHAN TEPUNG PUCUK Indigofera zollingeriana (Miquel, 1855) DALAM PAKAN UNTUK MENINGKATKAN KUALITAS WARNA IKAN SUMATRA Puntigrus tetrazone (Bleeker, 1855) - Enggi Rizki Pratama; Berta Putri; Luki Abdullah; Indra Gumay Yudha; Dwi Mulyasih (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Tiger barb (Puntigrus tetrazona) is one of the ornamental freshwater fish which has unique body shape and color compare to another ornamental fish. Fish color quality is caused by chromatophore pigmen cells in the epidermis layer. Increasing of color quality in fish can be reach through the addition of indigofera leaf meal that contain carotenoid. The aim of this research to study the effect of addition meal of Indigoferazollingerianaleaf on colour quality and growth of tiger barb. The experimental design used completely randomized design with 5 treatments i.e 0%, 5%, 10%, 15%, 20% of I. zollingeriana meal added in fish feed. The results showed that the addition of I. zollingeriana meal could increase tiger barb color quality. The addition of 15% I. zollingeriana meal was the best treatment